What works in medical education, where and why?. Issue 9 (22nd July 2019) - Benassi, Paul; Sockalingam, Sanjeev
Abstract : Benassi and Sockalingam argue that it is critical to understand the key ingredients of an intervention along with factors that influence implementation if we are to tanslate medical education research into practice.